The effect of temporal resolution of input rainfall data in hydrological modelling at urban catchment - Chow M.F.; Haris H.; Leong Y.X. (American Institute of Physics Inc., 2023)
The process of urbanization with increasing population and development has drastically disrupted the water balance of natural catchment. The variation in hydrological responses due to rainfall and land use changes increases the difficulty on rainfall-runoff modelling. In addition, large uncertainties in rainfall data can be a significant source of error in flood simulation. Thus, the objective of this study is to compare the temporal resolution effects between 15 min and 1-hour rainfall data on hydrological modelling at urban catchment. 15 min and 1-hour resolution rainfall data was collected from eight rainfall stations at Penchala River catchment. The temporal resolution effects of rainfall data on hydrological modelling were assessed by comparing 15 min resolution and 1-hour resolution rainfall data using HEC-HMS model. The modelling results showed that average peak discharge percentage errors for 1-hour rainfall interval is 15.79 %, whereas 4.33% for 15 minutes' rainfall interval. The fine resolution rainfall data has proved that it had improved the performance of hydrological modelling using HEC-HMS model. For model calibration, the mean percentage errors for peak discharge and runoff volume were found to be 4.33% and 20.88%, respectively. Meanwhile, the mean percentage errors for peak discharge and runoff volume for model validation were found to be 16.25% and 16.51%, respectively. 2021 American Institute of Physics Inc.. All rights reserved.